A Compact Tri-Band Bandpass Filter with High Out-of-Band Rejection - Abdul-Niby, M.; Farhat, M.; Nahas, M.; Alomari Μ. Μ. (Engineering, Technology & Applied Science Research, 2017)
This paper presents a planar tri-band bandpass filter with high out-of-band rejection over a wide band. The filter is based on two pairs of λ/4 resonators embedded inside an open loop ring resonator without any size increase, where each pair of resonators are electromagnetically coupled to each other and the feedlines. This results in the excitations of passbands, where the first passband is generated by the open loop resonators. The second and the third passbands are excited by λ/4 resonators. The proposed technique provides sufficient degrees of freedom to control the center frequency and bandwidth of the three passbands independently. In addition, the six transmission zeros created around the passbands results in a tri-band filter with high selectivity, sharp 3 dB cut-off frequency, high isolation, low passband insertion-loss and high out-of-band harmonic rejection across an ultra-broadband frequency range up to 17 GHz. The proposed technique has the ability to switch from triple to dual band by removing one pair of the inner resonators. Design methodology and simulation results of the filter are provided.